Development of a copro-LAMP assay for detection of several species of Echinococcus granulosus sensu lato complex - Avila, Héctor Gabriel (2020)
Cystic echinococcosis represents a significant problem in human and animal health and constitutes one of the most severe Neglected Tropical Diseases prioritized by the World Health Organization. The etiological agent is the complex Echinococcus granulosus sensu lato (s. l.), composed of several species/genotypes. Diagnosis in the definitive host and molecular epidemiology studies are important points for cystic echinococcosis control. Here we developed a new copro-LAMP assay, LAMP EGSL, for diagnosis in the definitive host for simultaneous detection of Echinococcus granulosus sensu stricto (s. s.), Echinococcus ortleppi, and Echinococcus canadensis species. Also, the analytical sensitivity, specificity and plausibility of performance in a rural context of a previously reported species-specific LAMP reaction, was evaluated. Both reactions showed high analytical sensitivity values (10 fg-100 fg DNA) and did not show cross reaction with DNA from host or other helminthic parasites. LAMP EGSL was performed with samples from an endemic area. In addition, the alkaline hydrolysis of one E. granulosus s. s. adult parasite followed by specific LAMP to E. granulosus s. s. was performed in a laboratory with low resources from another cystic echinococcosis endemic area. The results obtained suggest that LAMP EGSL represents a potential tool for canine diagnosis that could be useful for cystic echinococcosis control programs. In addition, we showed that LAMP reaction for E. granulous s. s., E. ortleppi and E. canadensis specific detection, could be useful for molecular epidemiology studies applicable to the definitive host. Both reactions were performed in endemic, rural areas without sophisticated equipment.